FERMENTASI KULIT NANAS MENGGUNAKAN CLOSTRIDIUM ACETOBUTYLICUM DENGAN VARIASI NUTRISI DAN INOKULUM - Sri Rezeki Mulia; Elvie Yenie; Mayang Sari (Jurnal Sains dan Teknologi, 2018)
Bioethanol is a fuel extracted from plant by fermentation process. Energy consumption increases steadily as world population increases and concerns about atmospheric pollution derived from fossil fuels have resulted in a worldwide interest in exploring for renewable energy in the form of bioenergy. The conversion of agriculture waste into biofuels so interesting now. The present study describes ethanol production from ananas waste by Clostridium acetobutylicum. This study was carried out to investigate the effect of variations inoculum, nutrition and fermentation time on the product yield resulting from fermentation using Clostridium acetobutylicum. The experiment was divided into three stages which included inoculum preparations, fermentation process and analysis. The result showed that the highest bioethanol production 9% was obtained at 8 days incubation period, using urea nutrition and 14% inoculum size. Bioethanol content increased with increasing fermentation time until 8 days after that decrease at 10 days. In contrast bioethanol concentration increased with increasing inoculum concentration until optimum condition. Nutrition urea better than using amonium sulphate.